2013
DOI: 10.1002/app.39696
|View full text |Cite
|
Sign up to set email alerts
|

Calculating hansen solubility parameters of polymers with genetic algorithms

Abstract: In materials engineering, it is often essential to know what are the best solvents to process any polymer, and employing methods based on Hansen solubility parameters are an effective way to find them. In this work the Hansen solubility parameters of polyether sulfone, lignin, and bitumen have been calculated by an alternative optimization procedure. It has been shown that, by applying an evolutionary strategy to Hansen's correlation method, it is possible to improve the fitting of solubility spheres. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 25 publications
2
78
2
Order By: Relevance
“…Recently, genetic algorithms were applied for calculating lignin HSPs ( Vebber et al 2014 ), and the obtained values (21.7, 14.2, 16.9, and 13.5 MPa 1/2 for δ D , δ P , δ H , and R 0 ) are in good agreement with previously published data ( Hansen and Bj ö rkman 1998 ). Based on these values, the REDs were calculated for each of the aforementioned solvents and compared with the amount of lignin solubilized x sol .…”
Section: Hspsmentioning
confidence: 91%
See 1 more Smart Citation
“…Recently, genetic algorithms were applied for calculating lignin HSPs ( Vebber et al 2014 ), and the obtained values (21.7, 14.2, 16.9, and 13.5 MPa 1/2 for δ D , δ P , δ H , and R 0 ) are in good agreement with previously published data ( Hansen and Bj ö rkman 1998 ). Based on these values, the REDs were calculated for each of the aforementioned solvents and compared with the amount of lignin solubilized x sol .…”
Section: Hspsmentioning
confidence: 91%
“…The HSPs of lignin used for the calculation could be the source of error. Lignin HSPs calculated by Hansen (1969) were referred to milled wood lignin (MWL), whereas Vebber et al (2014) gave no hints to the type of lignin considered. In view of the structural differences between KL and MWL, significant differences in terms of solubility parameters are expectable.…”
Section: Hspsmentioning
confidence: 99%
“…Our review of the literature revealed that the solubility parameters of a solute can vary significantly just by changing the algorithm used to compute the sphere, that is, even without changing the observed data, different spheres can be obtained using a different algorithm to fit the data. For example, independent calculations by Vebber et al 29 and Gharagheizi 30 for the d D , d P , and d H parameters of polyethersulfone (PES) vary individually by as much as 20%, and there is a 24% discrepancy in the computed radius of each Hansen sphere despite using the exact same data set.…”
Section: 33mentioning
confidence: 97%
“…Nevertheless, this gives rise to discussion of statistical measures such as sensibility (the proportion of all observed good solvents that lie inside the solubility region) and specificity (the proportion of all bad solvents that lie outside the solubility region). 29 4. The requirement of a spherical solubility space implies that the intermolecular interactions and thermodynamics related to the dispersive, polar, and hydrogen-bonding parameters equally influence the solubility behavior.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation